2020
DOI: 10.1002/alr.22626
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes in aspirin‐exacerbated respiratory disease without aspirin desensitization

Abstract: Background: Aspirin-exacerbated respiratory disease (AERD) represents a severe endotype of chronic rhinosinusitis with nasal polyposis. Although aspirin desensitization (AD) has emerged as an effective therapeutic option, the natural history of AERD without AD remains unclear. Methods: A retrospective review was conducted of AERD patients who underwent endoscopic sinus surgery (ESS) without AD between 2010 and 2019. The primary outcomes were revision surgery rate and time to revision surgery. Secondary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Similarly, in our study with a mean follow up time of approximately 10 months, only one patient required revision ESS and only after stopping dupilumab therapy due to an adverse reaction. The ability to reduce or delay the need for ESS and subsequent revision surgeries is an important consideration in this patient population who have a high propensity for multiple surgical interventions, particularly among patients with AERD [ 25 ]. This study had a large proportion of patients with AERD (41%) and further demonstrates effectiveness in this difficult-to-treat patient population in the real world setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in our study with a mean follow up time of approximately 10 months, only one patient required revision ESS and only after stopping dupilumab therapy due to an adverse reaction. The ability to reduce or delay the need for ESS and subsequent revision surgeries is an important consideration in this patient population who have a high propensity for multiple surgical interventions, particularly among patients with AERD [ 25 ]. This study had a large proportion of patients with AERD (41%) and further demonstrates effectiveness in this difficult-to-treat patient population in the real world setting.…”
Section: Discussionmentioning
confidence: 99%
“…The delay in initiating therapy with dupilumab is likely secondary to a multitude of factors including the fact that patients typically have improvement from surgery for approximately 1 year prior to seeking additional therapy in addition to insurance approval delays for obtaining the medication. 25 Additionally, the validity of this study is limited by its relatively small sample size of patients. Despite the limitations described here, our study suggests that in this cohort of patients, dupilumab treatment improves sinonasal symptoms and quality of life in patients with difficult-to-treat and medically refractory CRSwNP.…”
Section: Limitationsmentioning
confidence: 96%
“…If possible, surgeons managing AERD patients should be comfortable performing advanced aeration surgical procedures. Advanced aeration surgery such as Draf III has, in the setting of AERD, have been shown to have positive outcomes including greater quality of life, improved disease maintenance, and reduced polyp recurrence [ 78 , 79 ]. There is additional data that has emerged that complete sinus surgery followed by aspirin desensitization and long-term aspirin maintenance leads to long-term symptom disease control [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some AERD patient's polyps will reform as quickly as a few months after surgery [6,35]. More recent studies looking at CRSwNP and/or AERD patients noted 45-90% of them required recurrent surgery, some of this variability includes mixed population of patients (not just AERD patients), variable follow-up (18 months vs 5 years), and geographic variations [36,37]. A 2007 meta-analysis study found 40% of patients with CRSwNP had reoccurrence of polyps at 18months but did not look at AERD specifically [38].…”
Section: Functional Endoscopic Sinus Surgerymentioning
confidence: 99%
“…Two studies looked at AERD specific patients, Grose et al found in a retrospective study probability of remaining free of revision surgery: 98.2% at one year, 78.8% at 3 years and 44.8% at 5 years. In that cohort 16 patients were also placed on monoclonal antibody therapy (omalizumab, mepolizumab, or both) [37]. One study showed a 5 year rate of polyp free symptoms of only 10% in AERD patients vs 84% CRSwNP but NSAID tolerant [36].…”
Section: Functional Endoscopic Sinus Surgerymentioning
confidence: 99%